Li and Fa in Contract Law from the Perspective of Chinese Legal Philosophy - Putro, Widodo Dwi; Tanya, Debora Jessica Desideria; Martini, Dwi (Universitas Negeri Semarang, 2024)
Traditional Chinese law is strongly influenced by two schools of thought, namely Confucianism which emphasizes “rule by li” and Legalism which emphasizes “rule of fa”. Both schools of thought have different accentuations, specifically, “li” emphasizes trust, while “fa” prioritizes certainty. In light of this ambivalence, this research seeks to address the following problem formulation: (i) how do the principles of